Strategi Pengembangan Desa Wisata Berdasarkan Rencana Induk Pembangunan Kepariwisataan Daerah Tahun 2015 – 2025 Dinas Pariwisata Kabupaten Sleman, Provinsi Daerah Istimewa Yogyakarta - Khusnina Almas Widya Motik; Lukman Arif (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Sleman Regency Government is one of the regions that enjoys the results of the tourism sector. According to data from the Sleman Regency Tourism Office (Dispar), in 2023 more than 60% of income in the tourism sector will come from cultural tourism, including village tourism and visits to temples and museums. Until semester 1 of 2023, the realization of PAD for Sleman Regency specifically in the tourism sector has reached IDR 164.8 billion or the equivalent of 54.72% of what was targeted. The issuance of Regional Regulation no. 11 of 2015 concerning the Tourism Development Master Plan (RIPK) shows the important role of Tourism Villages and the strategy of Sleman district in organizing tourist areas. The aim of this research is to analyze the Tourism Village development strategy based on (RIPK) Sleman Regency. The research method in this study uses qualitative research by collecting data through interviews, observation and literature study. The results of this research show firstly that the empowerment efforts carried out by the Sleman Regency Tourism Office have been carried out for years and have proven successful. Second, the tourism village program which is pro-poor can be said to be successful. Third, decentralization efforts can be said to be successful. This is realized through several programs that have been well implemented by the government. Fourth, participation efforts from tourist villages in Sleman Regency can be said to be successful. This is realized through community involvement in MUSREMBANG and supervision in terms of managing tourist villages. The five supports for women in developing tourist villages in Sleman Regency can be said to be successful because women have received great benefits. Sixth, self-sufficiency can be said to be successful through collaboration and innovation which is the key to the success of tourist villages. Seven, The integration of development programs has been realized through efforts, namely the construction of physical buildings, poverty training, and empowerment efforts through training have also been carried out